LSD Administered as a Single Dose Reduces Alcohol Consumption in C57BL/6J Mice - Alper, Kenneth; Dong, Bin; Shah, Relish; Sershen, Henry; Vinod, K. Yaragudri (Frontiers in Pharmacology, 2018)
There is a substantive clinical literature on classical hallucinogens, most commonly lysergic acid diethylamide (LSD) for the treatment of alcohol use disorder. However there has been no published research on the effect of LSD on alcohol consumption in animals. This study evaluated the effect of LSD in mice using a two-bottle choice alcohol drinking paradigm. Adult male C57BL/6J mice were exposed to ethanol to develop preference and divided into three groups of equal ethanol consumption, and then treated with single intraperitoneal injection of saline or 25 or 50 µg/kg LSD and offered water and 20% ethanol. The respective LSD-treated groups were compared to the control group utilizing a multilevel model for repeated measures. In mice treated with 50 µg/kg LSD ethanol consumption was reduced relative to controls (p= 0.0035), as was ethanol preference (p= 0.0024), with a group mean reduction of ethanol consumption of 17.9% sustained over an interval of 46 days following LSD administration. No significant effects on ethanol consumption or preference were observed in mice treated with 25 µg/kg LSD. Neither total fluid intake nor locomotor activity in the LSD-treated groups differed significantly from controls. These results suggest that classical hallucinogens in the animal model merit further study as a potential approach to the identification of targets for drug discovery and investigation of the neurobiology of addiction.